ANALYSIS OF SOCIAL DEIXIS IN THE MOVIE FULL METAL JACKET - Jatmiko, J; Tri, Oki; Laila, Malikatul (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
This research deals with the implementation of social deixis in the movie Full Metal Jacket (1987). It aims to find out the kinds of social deixis and to explain the social relationship between the characters utterances in the movie Full Metal Jacket (1987) which contains social deixis. This research using descriptive qualitative method and implementing purposive sampling data collection techniques. As the result, the researcher found two kinds of social deixis such as relational social deixis and absolute social deixis. In this research also found that relational social deixis used more dominant by the character in the movie Full Metal Jacket (1987) than the absolute social deixis.